Apulian infectious diseases network: survey on the prevalence of delta infection among chronic HBV carriers in Apulia - Fasano, Massimo; Milella, Michele; Carbonara, Sergio; Tundo, Paolo; Minniti, Salvatore; Buccoliero, Giovanni; Maci, Anna Maria; Lo Caputo, Sergio; Santantonio, Teresa Antonia (Frontiers in Public Health, 2023)
Background The current prevalence and clinical burden of Hepatitis Delta Virus (HDV) infection in Apulia are unknown. This study aimed to define the current epidemiological scenario of delta infection and to detect difficulties in the diagnosis and clinical management of HDV patients in Apulia. Methods From May to September 2022, a fact-finding survey was conducted at eight Infectious Diseases Units of the Apulian region; each Unit was asked to complete a questionnaire on screening and diagnosis of HDV infection and demographic, virological, and clinical characteristics of HDV patients. Results A total of 1,461 HBsAg-positive subjects were followed up on an outpatient basis. Screening for HDV ranged from 30 to 90% of HBsAg + carriers in a single center. Overall, 952 HBsAg ± subjects (65%) were tested for HDV, and 80/952 (8.4%) were anti-HDV positive. Serum HDV RNA was detected only in 15/80 (19%) anti-HDV-positive subjects, and 12/15 patients (80%) were viremic. Sixty-five anti-HDV-positive subjects (81%) were from Italy; risk factors for HDV acquisition included the presence of HDV infection in the family (29/80 = 36%), drug addiction (12/80 = 15%), and co-infection with HCV or HIV (7/80 = 9%). Liver cirrhosis and hepatocellular carcinoma were diagnosed in 41 (51%) and 4 (5%) patients, respectively. Fifty-seven patients (71%) received nucleos(t)ide analog treatment. Conclusions The results of this survey show that HDV screening is variable and insufficient, thus real prevalence data on delta infection are lacking in Apulia. Moreover, the HDV RNA test is not available in most laboratories and is not provided by the national health system. These results underline the need for an organizational model to optimize the management of HDV patients throughout the Apulian region.